Exploração de aves Columbidae no interior de Sergipe (Brasil): diferentes olhares sobre uma prática enraizada - Silva, Cleverton da (2023)
Birds are among the most hunted animal groups worldwide. Representatives of the Columbidae family (doves, pigeons and relatives; henceforth columbids) are among the main targets for food purposes and, consequently, suffer considerable hunting pressure, especially in the Northeast region of Brazil, where they are hunted unsustainably. That said, this research sought to investigate: 1) how columbidae are exploited in three rural areas in the municipality of Itabaiana (Sergipe, Brazil); 2) the current status of populations of these birds in the region; and 3) the perception of residents, researchers (academics) and IBAMA inspectors, all from the region, about hunting columbids. The results revealed seven species of Columbidae that are hunted in large quantities in the region, preferably with the use of pellet shotguns, to be used mainly as a food resource. As reported by local hunters, these species are preferably hunted during the dry season and at night. The study also revealed that most of the Columbidae species recorded in the region were more abundant in the rainy season and more than half had low abundances and a tendency to decline throughout the year. Furthermore, it was revealed that most local residents make regular use of columbids, mainly as a food resource, suggesting controlled hunting as a way of reconciling the practice of hunting with the conservation of this group of birds. IBAMA inspectors and researchers are against hunting and believe that improving the socioeconomic condition of residents, in particular, can mitigate this problem in the region. Taken together, these results demonstrate that the ban on hunting in Brazil was not enough to mitigate or eradicate the hunting of columbids in the region. It is possible that hunting is responsible for the low population abundances of columbids sampled. It is important to stress, however, the importance of these birds as a food resource for local rural communities. Thus, it is necessary to discuss the possibility of transitioning from a popular, but uncontrolled hunting culture to a condition of sustainable and scientifically based management, capable of preventing the decline and loss of species in the long term.